2016
DOI: 10.3847/0004-637x/826/2/167
|View full text |Cite
|
Sign up to set email alerts
|

The Massive Survey. Iv. The X-Ray Halos of the Most Massive Early-Type Galaxies in the Nearby Universe

Abstract: Studies of the physical properties of local elliptical galaxies are shedding new light on galaxy formation. Here we present the hot-gas properties of 33 early-type systems within the MASSIVE galaxy survey that have archival Chandra X-ray observations, and we use these data to derive X-ray luminosities (L X,gas ) and plasma temperatures (T gas ) for the diffuse gas components. We combine this with the ATLAS 3D survey to investigate the X-ray-optical properties of a statistically significant sample of early-type… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
156
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(177 citation statements)
references
References 134 publications
(255 reference statements)
18
156
1
Order By: Relevance
“…However, with only redshifted emission, we cannot rule out an inflow, rotation, or simply an ongoing merger. We do detect a compact radio source (K. Nyland et al in preparation) and a soft nuclear X-ray source (Goulding et al 2016) in the center. Since we do not detect Hβ we cannot say much about the nuclear line ratios.…”
Section: Special Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with only redshifted emission, we cannot rule out an inflow, rotation, or simply an ongoing merger. We do detect a compact radio source (K. Nyland et al in preparation) and a soft nuclear X-ray source (Goulding et al 2016) in the center. Since we do not detect Hβ we cannot say much about the nuclear line ratios.…”
Section: Special Casesmentioning
confidence: 99%
“…The relationship between the warm ionized and hot X-ray-emitting gas is still unclear (e.g., Forman et al 1985;H e c k m a ne ta l .1989; Macchetto et al 1996;Goudfrooij 1999;Sarzi et al 2013;Goulding et al 2016),andwe have approved Chandra time (PI: Goulding) to increase the MASSIVE sample with hot gas measurements. Similarly, the occurrence rate of warm ionized gas (and dust) as a function of radio continuum detection may reveal relationships to accreting supermassive black holes and the presence of central dust disks; this will be explored in a future study.…”
Section: Future Work and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray scaling relations have been widely used to investigate the origin and evolution of the hot ISM of ETGs [1][2][3][4]. Recent numerical simulation studies [5][6][7][8] have further attempted to reproduce the observed scaling relations, in order to constrain the physical mechanisms that shape the hot ISM.…”
Section: X-ray Scaling Relationsmentioning
confidence: 99%
“…This relation is tighter than the L X,GAS -L K relation and may indicate virialization of the hot gas in the dark matter halos. The best fit relation is L X,GAS~TGAS 4.5 [1,3,4] when the cD galaxies are excluded. The relation is particularly tight for the normal (non-cD) core galaxies with a scatter of only 0.2 dex rms.…”
Section: Xgas -T Gas Relationmentioning
confidence: 99%